Pediatric May‐Thurner Syndrome—Systematic review and individual patient data meta‐analysis. (1st April 2021) - Avila, Laura; Cullinan, Noelle; White, Michael; Gaballah, Marian; Cahill, Anne Marie; Warad, Deepti; Rodriguez, Vilmarie; Tarango, Cristina; Hoppmann, Anna; Nelson, Stephen; Kuhn, Tomas; Biss, Tina; et al.
Abstract: Background: The outcomes of deep vein thrombosis (DVT) in children with May‐Thurner Syndrome (MTS) remain unclear. Objectives: This systematic review and patient‐level meta‐analysis aims to describe the outcomes of children with MTS presenting with DVT. Methods: A systematic review of the published literature was performed. Data related to patients <18 years diagnosed with MTS and DVT was extracted. Risk of bias was assessed using the Murad criteria. Outcomes included vessel patency post‐treatment, DVT recurrence, and post‐thrombotic syndrome (PTS). Predictive and explanatory models were developed for these outcomes. Results: In total, 109 cases were identified (age range 4–17 years; 77 females) in 28 studies; 75% of patients had ≥1 additional risk factor for DVT. PTS was seen in 61% of patients, DVT recurrence in 38%, and complete vessel patency post‐treatment in 65%. The models developed to predict and explain PTS performed poorly overall. Recurrent thrombosis (adjusted for age and patency) predicted PTS (odds ratio [OR] 3.36, 95% confidence interval [CI] 1.28–8.82). DVT management strategies (adjusted for age and DVT characteristics) predicted vessel patency (OR 2.10, 95% CI 1.43–3.08). Lack of complete vessel patency (adjusted for age and thrombophilia) predicted recurrent DVT (OR 2.70, 95% CI 1.09–6.67). Sensitivity analyses showed the same direction of effects for all outcomes. Conclusions: PTS and DVT recurrence occur frequently in pediatric MTS. PTS prediction is complex and it was not possible to identify early predictors to guide clinical practice. Use of imaging‐guided therapy and thrombus burden predicted venous patency, and lack of patency predicted DVT recurrence.